Online Learning Readiness, Accounting Automation and Learning Process - Ferry Kosadi; Devyanthi Syarief; Kartika Berliani; Muhammad Iqbal Alamsyah (JAF (Journal of Accounting and Finance), 2022)
This research was conducted to evaluate the increase in intention to contribute to the automation of accounting in order to increase digital literacy and formulate virtual learning patterns of computerized accounting practice. There are obstacles in online learning in the form of the effectiveness of learning outcomes, especially on practical materials to improve skills or proficiency in mastering computerized accounting, accompanied by a gap in understanding in the technical field of design and automatic transaction processing with programming language instructions for accounting application design. Experimental designed through the stages of practicing on cloud-based accounting followed by a diffusion stage of practice through spreadsheet applications with automation program instructions as a mediator for increasing digital literacy. Analyze with PLS-SEM to evaluate between online learning readiness, computerized accounting and digital automation with learning process. The novelty is to focus on the technical learning of accounting computerized practices completed by automation processing with algorithms and programming scripts to enhance digital literacy. The results indicate a significant increase in the intention to improve digital literacy and contribute to the development of accounting automation & digitization as well as understanding of program language and application design. There is an increasing intention to contribute to the development of automation and digitalization of accounting by the process of repeated exercise (diffusion) through a certain pattern that indirectly increasing their digital literacy.